Biomineralized Gd2O3@HSA Nanoparticles as a Versatile Platform for Dual‐Modal Imaging and Chemo‐Phototherapy‐Synergized Tumor Ablation. Issue 24 (18th November 2019) - Hao, Tangna; Chen, Qixian; Qi, Yan; Sun, Pengyuan; Chen, Dawei; Jiang, Weiwei; Liu, Kexin; Sun, Huijun; Li, Lei; Ding, Jianxun; Li, Zhen
Abstract: A great challenge still remains to explore the facile approaches to construct multifunctional nanoparticles for acquiring precise cancer theranostics. Herein, a biocompatible theranostic nanoplatform capable of simultaneous cancer imaging and therapy is attempted by loading of paclitaxel (PTX) and indocyanine green (ICG) molecules into the matrix of Gd2 O3 @human serum albumin (HSA) nanoparticles (PIGH NPs) via hydrophobic interaction. The subsequent in vitro investigations reveal that the PIGH NPs afford uniform particle size, sustained drug release profile, strong longitudinal relaxivity, potent photothermal effect, effective singlet oxygen generation, and ideal resistance to photobleaching. Moreover, the PIGH NPs achieve high cellular uptake, efficient cytoplasmic drug translocation based on singlet oxygen‐triggered endolysosomal disruption and prominent cytotoxicity effect against 4T1 cells under 808 nm near‐infrared (NIR) irradiation in contrast to PTX/ICG‐loaded HSA nanoparticles (PIH NPs) and free PTX/ICG. After intravenous injection, the PIGH NPs exhibit preferable tumor accumulation and achieve effective tumor ablation in 4T1 tumor bearing mouse model with excellent dual near‐infrared fluorescence/magnetic resonance (NIRF/MR) imaging guided synergistic chemo‐phototherapy. Hence, the PIGH NPs can be utilized as potential theranostic nanosystem for simultaneous cancer imaging and therapy. Abstract : A biocompatible theranostic nanoplatform capable of simultaneous cancer imaging and therapy by loading of indocyanine green (ICG) and paclitaxel (PTX) molecules into the matrix of Gd2 O3 @HSA nanoparticles is developed, suggesting its huge potential for clinical applications.